Electroless‐coated magnetic three‐dimensional graphene with silver nanoparticles used for the determination of pesticides in fruit samples. Issue 7 (23rd March 2018) - Sereshti, Hassan; Afsharsaveh, Zahra; Gaikani, Hamid; Rashidi Nodeh, Hamid
Abstract: A new type of adsorbent composed of magnetic three‐dimensional graphene coated with silver nanoparticles was synthesized by an electroless technique and used in the magnetic solid‐phase extraction of selected pesticides (fenitrothion, chlorpyrifos, and hexaconazole) before gas chromatography with a micro‐electron capture detector. The adsorbent was characterized using Fourier‐transform infrared spectroscopy, X‐ray diffraction, vibrating sample magnetometry, and field‐emission scanning electron microscopy. The important extraction parameters such as pH, adsorbent dose, extraction time, and desorption conditions were investigated. Under the optimal conditions, the analytical figures of merit were obtained as: linear dynamic range of 0.1–5 ng/g with determination coefficients of 0.991–0.996; limit of detection of 0.07–0.13 ng/g; limit of quantification of 0.242–0.448 ng/g; and the intraday and interday relative standard deviations ( C  = 5 ng/g, n  = 3) were 3.8–8.7 and 6.6–8.9%, respectively. The developed method was successfully applied for analysis of the selected pesticides in tomato and grape with extraction recoveries in the range of 72.8–109.6%.